Thyroid-Like Ophthalmopathy in a Euthyroid Patient Receiving Ipilimumab. (December 2014) - McElnea, Elizabeth; Ní Mhéalóid, Áine; Moran, Sarah; Kelly, Rory; Fulcher, Tim
Abstract A 68-year-old lady with metastatic malignant melanoma was treated with Ipilimumab. She presented to Eye Casualty unable to move her eyes. Physical examination confirmed ophthalmoplegia and identified proptosis bilaterally. Radiological imaging showed bilateral enlargement of all the extra-ocular muscles suggestive of thyroid eye disease. Laboratory investigations found this patient to be euthyroid. A diagnosis of thyroid-like orbitopathy secondary to Ipilimumab therapy was made. Thyroid function tests should be performed for all patients prior to their commencement of Ipilimumab. Thyroid-like eye disease may develop in patients treated with Ipilimumab even if they remain euthyroid.